Through the Intestines to the Head? That Is, How the Gastrointestinal Microbiota Affects the Behavior of Companion Animals - Zofia Gorzelanna; Marta Miszczak (Pets)
Microbiome research has become significantly advanced in recent years, both in human and veterinary medicine. The development of DNA sequencing technology has enabled a deeper understanding of the diversity of microorganisms inhabiting animal bodies. It has given clinicians, scientists, and behaviorists a chance of better understanding the impact that a proper microbial population has on the individual, enabling a much more holistic view of the animals’ health and welfare. Current knowledge is increasingly based on analyses of the impact of microorganisms present in the gastrointestinal tract on the neurobiology and behavior of the host. This review presents research results, indicating potential implications for fields such as ethology and veterinary medicine. Understanding the role of the microbiome in shaping animal behavior could open up new therapeutic opportunities and lead to more sustainable animal husbandry practices.